Socio Cultural Literacy of The Buffer Zone Community Towards Preservation of The Gunung Halimun Salak National Park (TNGHS) - Rusmana, Agus; Rizal, Edwin; Khadijah, Ute Lies (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
The area of Gunung Halimun Salak National Park as the Halimun Ecosystem Zone is a mountain zone in Jawa Barat which has a high bio diversity. The traditional or local community have managed its natural resources by oriented it toward their interests. The completeness of its area ecosystem is fully depended on the buffer zone community. This research is identifying the socio cultural literacy of buffer zone community towards preservation of the Gunung Halimun Salak National Park. The method used is qualitative approach which used the members of the community as informants. The result of the research show that the buffer zone